Neither Aerobic Interval nor Circuit Resistance Exercise Acutely Enhance Glucose Tolerance in Healthy, Young Adults - William A. Braun; Nathaniel Helwig; W. Jeffrey Armstrong (Asian Society of Kinesiology, 2024)
Physical activity and glycemic control are important factors in preventing chronic disease such as Type II diabetes. Glycemic control may be enhanced during recovery from acute exercise. OBJECTIVES To test the effects of resistance exercise (RT) vs. aerobic interval exercise (AER) on post-exercise blood glucose (BG) control during an oral glucose tolerance test (OGTT). METHODS Ten volunteers completed three separate trials (counter-balanced order): a resting control trial (CON) consisting of a 75-min OGTT following consumption of a 25% glucose solution dosed at 1 g/kg body mass; a RT trial in which subjects completed a 30-min circuit protocol (6-7 sets) of 6 reps/set using 10-RM load for squat, bench press, knee extension and biceps curl; and the AER trial where subjects alternated between treadmill exercise (3 min) and arm crank ergometry (2-min) over a 30-min period (intensity target of 15 on the Borg 6-20 point Rating of Perceived Exertion scale). Both exercise trials were followed by the same 75-min OGTT. BG was assessed via fingertip sampling prior to exercise, mid-exercise, post-exercise, and every 15-min during the OGTT. Blood lactate was collected at rest, mid-exercise, post-exercise and at 15 min of the OGTT. RESULTS Both exercise trials elicited significantly increased lactate but were not different from one another. BG was significantly elevated during the OGTT for all conditions but was not different by condition. BG area under the curve (AUC) was 5.6% smaller (p>0.05) following RT and AER vs. CON (CON: 10687±381; RT: 10087±343; AER: 10093±299 arbitrary units). CONCLUSIONS Acute resistance and aerobic interval exercise were not found to elicit significantly enhanced post-exercise glycemic control. Post-exercise glycemic control may be related to the total energy deficit achieved in young, healthy adults.